ANALYSIS OF DISCOUNT PRICING AND MARKETING OF PROCESSED CATFISH IN KWARA STATE, NIGERIA - SALAU, S. A.; NOFIU, N. B.; JIMOH, A. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
In the literature, there are few researches on the effect of discount pricing on the market margin of catfish marketers. Consequently, this study identified the common types of price discounts and discount pricing strategies, described the catfish market’s structure, estimated marketing margin, determined variables affecting price discounting strategies and identified the constraints hindering price discounting among marketers in the study area.  Two hundred and twelve respondents were selected proportionately. To achieve the objectives of this study, the Likert-type scale, Herfindal Index, marketing efficiency as well as marketing margin and multiple regression analysis were used.  The Herfindahl index value of 0.006 was obtained, which suggested an extremely aggressive and expanded catfish market. A marketing efficiency value of (140.09%), indicated that catfish marketing was well organised. The marketing margin value of 28.62%, implied that every ₦1 deal evolves a price spread of about 0.29k in catfish marketing. Hence, catfish marketing is profitable and is therefore worthwhile. The marketing margin, cost of spoilt fish, cost of marketing services, pond size and distance to state capital are the predictors of price discounting among marketers. In addition, the study revealed that the most significant constraint hindering discount pricing strategies in catfish marketing is the cost of production. We, therefore, recommend training marketers on the productive methods of processing and storing catfish in order to reduce losses and raise marketing margins. The pooling of resources together is also encouraged to minimise the cost of production. Policies towards increasing pond sizes should be enhanced by the government at all levels.